Pengaruh Brand Image, Word Of Mouth, Promosi Dan Harga Terhadap Keputusan Pembelian Pada Sosial Commerce Scarlett Whitening Di Shopee (Studi Kasus Pada Mahasiswi Kec. Lowokwaru Kota Malang) - Rosyidah, Ainul Fitrotur; Arifin, Rois; Mahardani, Ahmad Subhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to examine and explain the influence of brand image, word of mouth, promotion, and price on purchasing decisions on Social Commerce Scarlett Whitening at Shopee (Case Study on Female Students in Lowokwaru District, Malang City). The sampling technique uses a non-probability sampling method with purposive sampling techniques. In this study, the population size is unknown, therefore this study uses the Malhotra formula to determine the number of samples by getting results as many as 80 respondents. Data collection method using online questionnaire (Google Form) For data analysis using SPSS Version 25 software to analyze instrument tests, classical assumption tests, hypothesis tests, multiple linear regression tests, and determination coefficient tests. The results of this study show that brand image, word of mouth, promotion, and price have a positive and significant effect simultaneously and partially on purchasing decisions. Meanwhile, the influence of brand image, word of mouth, promotion, and price on purchasing decisions showed a determination value of 61.6%. Keywords: Brand Image, Word of Mouth, Promotion, Price, and Purchasing Decision.